One Family, Different Experiences of Identity Formation: International Graduate Students and Their Spouses - de la serna, Ana X. (Journal of International Students, 2021)
In this study, we use the communication theory of identity (CTI) to analyze the disparate experiences of International Graduate Students (IGS) and their accompanying partners. In CTI, four layers constitute the concept of identity: (a) The way individuals see themselves (personal), (b) their communicative interaction through social roles (relational), (c) their construction of messages (enactment), and (d) their role within a group or social network (communal). Thus, CTI views identity as a communicative and relational phenomenon. We analyze the layers of identity of IGS and their spouses living in the United States and find that although there are some coincidences, individuals within the studentdependent dyad mostly do not follow a common path of re-construction of their identity frames. Each narrative reflects individual and dyads’ struggles as they work to define their new identities. For this phenomenological study, we conduct individual in-depth interviews with 16 couples from 12 different countries.